Metabolic reprogramming shapes the immune microenvironment in pancreatic adenocarcinoma: prognostic implications and therapeutic targets - Song, Weihua; Yu, Yabin; Wang, Siqi; Cui, Zhengyi; Zhu, Qiusi; Liu, Wangrui; Wei, Shiyin; Chi, Jiachang (Frontiers in Immunology, 2025)
IntroductionPancreatic adenocarcinoma (PAAD) is characterized by a profoundly immunosuppressive tumor microenvironment (TME) that limits the efficacy of immunotherapy. Emerging evidence suggests that tumor-specific metabolic reprogramming may drive disease progression and shape the immune landscape in PAAD.MethodsWe integrated multi-omics data from TCGA, GEO, and ICGC to identify key metabolism-related genes (MRGs) that influence immune cell infiltration, tumor progression, and patient survival. Based on nine pivotal MRGs (including ANLN, PKMYT1, and HMGA1), we developed and validated a novel metabolic-prognostic index (MPI). Functional enrichment analyses were conducted to elucidate the metabolic pathways associated with different MPI risk groups. In vitro experiments and drug sensitivity analyses were performed to confirm the oncogenic role of selected MRGs and to explore their therapeutic implications.ResultsThe MPI effectively stratified patients into high- and low-risk groups. High-MPI scores correlated with poor overall survival, elevated tumor mutation burden (TMB), and an immunosuppressive TME, evidenced by reduced CD8⁺ T-cell infiltration and increased expression of immune checkpoints (PD-L1, TGF-β). Functional enrichment revealed glycolysis and folate biosynthesis as dominant pathways in high-MPI groups, whereas fatty acid metabolism prevailed in low-MPI groups. Experimental validation underscored the role of ANLN in promoting epithelial-mesenchymal transition (EMT) and immune evasion via NF-κB signaling. ANLN knockdown significantly reduced glycolytic activity, tumor cell migration, and immune evasion. Drug sensitivity analyses indicated resistance to gemcitabine but sensitivity to afatinib in high-MPI patients. Although TIDE analysis predicted immune checkpoint inhibitor (ICI) resistance in high-MPI tumors, a subset of patients showed favorable responses to anti-PD-L1 therapy.DiscussionThese findings provide a comprehensive framework for understanding how metabolic reprogramming shapes PAAD’s immunosuppressive TME and affects treatment outcomes. By accurately stratifying patients, the MPI serves as a promising tool to guide therapeutic decisions, including targeted therapy selection and immunotherapy prediction, ultimately offering potential for more personalized management of PAAD.